Control of mach 2 jet using sonic coflow. Issue 2 (August 2020) - Sharma, Keshav Ramesh; Akash, A; Vishal, R; Rajkumar, S; Bharadwaj, K K; Aravindh Kumar, S M
Abstract: An experimental investigation was done to understand the effect of sonic coflow jet on the core length of Mach 2 jet at different levels of expansion. The sonic jet surrounding the primary Mach 2 jet was produced using a sonic nozzle, whereas a convergent-divergent nozzle was used for Mach 2 jet. The annular gap between the sonic and supersonic nozzles was 1mm. For a fixed main jet NPR, the NPR of the sonic jet was varied from 4 to 6 (in steps of 1), which correspond to underexpanded levels of the sonic jet. The NPR of Mach 2 jet was varied from 4 to 6, which correspond to overexpanded states of Mach 2 jet. Without sonic coflow, the core length of Mach 2 jet was found to increase with the increase of NPR which was quantified using shadowgraph visualization. For all the main jet NPRs, the increase in coflow NPR resulted in the increase of core length. For each NPR of Mach 2 jet, the core length increases with the increase of coflow NPR. The maximum core length for NPRs 4 to 6 was at coflow NPR of 6 and minimum was at coflow NPR 4. The sonic coflow was found to retard the mixing of Mach 2 jet at all the pressure ratios, but it resulted in weakening the strength of waves present in the core of Mach 2 jet.